Medical complications associated with substance use disorders in patients with type 2 diabetes and hypertension: electronic health record findings. (25th April 2019) - Winhusen, Theresa; Theobald, Jeff; Kaelber, David C.; Lewis, Daniel
Abstract: Background and Aims: Screening for substance use disorder (SUD) in general medical settings may be particularly important in patients with comorbid health conditions exacerbated by SUD. This study evaluated whether SUD is associated with type 2 diabetes mellitus (T2DM) complications in patients with co‐occurring T2DM and hypertension. Design: Analysis of a limited data set obtained through IBM Watson Health Explorys, a platform integrating data from electronic health records. Matched controls were defined for each of five SUDs: tobacco use disorder (TUD), opioid use disorder (OUD), cocaine use disorder, cannabis use disorder (CUD) and alcohol use disorder (AUD) using Mahalanobis distance within propensity score calipers. Setting: All patients were seen in the MetroHealth System (Cleveland, OH, USA) and had diagnosis codes for T2DM and hypertension. Participants: SUD group participants had a diagnosis of abuse/dependence for the substance of interest. Controls for each SUD group had no diagnosis code related to the SUD of interest and were selected to match the SUD patients on demographics, residential zip code median income and body mass index. Total sample sizes for each SUD–control comparison ranged from 1160 for CUD to 22 128 for TUD. Measurements: Outcome was diagnosis (yes/no) of four T2DM complications (cerebrovascular accident, diabetic neuropathy, diabetic renal disease, myocardial infarction) and all‐cause mortality. Findings: Logistic regressions revealed that SUD was significantly associated with greater risk of cerebrovascular accident [TUD odds ratio (OR) = 1.79, OUD‐OR = 1.94, cocaine use disorder OR = 2.67], diabetic neuropathy [TUD‐adjusted OR (aOR) = 1.47, cocaine use disorder‐aOR = 1.35, AUD‐aOR = 1.27], diabetic renal disease (TUD‐aOR = 1.25, OUD‐OR = 1.34), myocardial infarction (TUD‐OR = 1.96, OUD‐OR = 2.01, cocaine use disorder‐OR = 2.68, CUD‐OR = 2.48, AUD‐OR = 1.42) and mortality (TUD‐OR = 1.15, cocaine use disorder‐OR = 1.61, CUD‐OR = 1.49, AUD‐OR = 1.35). Conclusions: Among patients in Ohio USA with both type 2 diabetes mellitus (T2DM) and hypertension, those with substance use disorders appear to have greater risk for T2DM complications and all‐cause mortality.